Label-free (fluorescence-free) sensing of a single DNA molecule on DNA origami using a plasmon-enhanced WGM sensor - Ghamari Shahin; Chiarelli Germán; Kołątaj Karol; Subramanian Sivaraman; Acuna Guillermo P.; Vollmer Frank (Nanophotonics)
The integration of DNA origami structures with opto-plasmonic whispering gallery mode (WGM) sensors offers a significant advancement in label-free biosensing, overcoming the limitations of traditional fluorescence-based techniques, and providing enhanced sensitivity and specificity for detecting DNA hybridization events. In this study, DNA origami acts as a scaffold for the precise assembly of plasmonic dimers, composed of gold nanorods (AuNRs), which amplify detection sensitivity by generating strong near-field enhancements in the nanogap between the nanorods. By leveraging the strong electromagnetic fields generated within the nanogap of the plasmonic dimer, this platform enables the detection of transient hybridization events between DNA docking strands and freely diffusing complementary sequences. Our findings demonstrate that the salt concentration critically influences DNA hybridization kinetics. Higher ionic strengths reduce electrostatic repulsion between negatively charged DNA strands, thereby stabilizing duplex formation and prolonging interaction times. These effects are most pronounced at salt concentrations around 300–500 mM, where optimal conditions for duplex stability and reduced dissociation rates are achieved. By thoroughly investigating the hybridization kinetics under varying environmental conditions, this study contributes to a deeper understanding of DNA interactions and offers a robust tool for single-molecule detection with real-time capabilities.